Finding a Toll on the Route: The Fate of Osteoclast Progenitors After Toll-Like Receptor Activation - Souza, Pedro P. C.; Lerner, Ulf H. (Frontiers in Immunology, 2019)
M-CSF and RANKL are two crucial cytokines stimulating differentiation of mature, bone resorbing, multinucleated osteoclasts from mononucleated progenitor cells in the monocyte/macrophage lineage. In addition to the receptors for M-CSF and RANKL, osteoclast progenitor cells express receptors for several other pro- and anti-osteoclastogenic cytokines, which also regulate osteoclast formation by affecting signaling downstream M-CSF and RANKL receptors. Similar to many other cells originating from myeloid hematopoetic stem cells, also osteoclast progenitors express toll-like receptors (TLRs). Nine murine TLRs are expressed in the progenitors and all, with the exception of TLR2 and TLR4, are downregulated during osteoclastogenesis. Activation of TLR2, TLR4 and TLR9, but not TLR5, in osteoclast progenitors stimulated with M-CSF and RANKL arrests differentiation along the osteoclastic lineage and keeps the cells at a macrophage stage. When the progenitors are primed with M-CSF/RANKL and then stimulated with agonists for TLR2, TLR4 or TLR9 in the presence of M-CSF, but in the absence of RANKL, the cells differentiate to mature, bone resorbing osteoclasts. TLR 2, 4, 5 and 9 are also expressed on osteoblasts and their activation increases osteoclast differentiation by an indirect mechanism through stimulation of RANKL. In mice, treatment with agonists for TLR2, 4 and 5 results in osteoclast formation and extensive bone loss. It remains to be shown the relative importance of inhibitory and stimulatory effects by TLRs on osteoclast progenitors and the role of RANKL produced by TLR stimulated osteoblasts, for the bone resorbing effects in vivo.